Super-strong weather-resistant rock plate and steel grit double-component ceramic tile back adhesive and preparation method thereof

By adopting a two-component structure and specific preparation technology of super-weather resistant rock sheet gold steel sand in ceramic tile backing, the shortcomings of existing backing backing in weather resistance, bonding strength and chemical corrosion resistance are solved, and a higher degree of resistance is achieved. Performance stability and adaptability, suitable for complex usage scenarios.

CN119462009AInactive Publication Date: 2025-02-18FOSHAN YONGLAN BUILDING MATERIALS COATING TECH CO LTD

Patent Information

Application Number
CN202411594368.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing ceramic tile backings have poor performance in weather resistance, bonding strength and chemical corrosion resistance, making it difficult to meet the needs of complex natural environments and special use scenarios. At the same time, the preparation process has problems of uneven stirring and poor compatibility.

Method used

The super-strong weathering rock sheet gold steel sand two-component ceramic tile backing is adopted. Through careful preparation of powder components and emulsion components and specific preparation processes, each component is ensured to be fully and evenly mixed, and the performance stability of the backing is improved.

Benefits of technology

Maintain good performance stability in complex natural environments, avoid aging and cracking, improve bond strength and adaptability, significantly improve chemical corrosion resistance, extend service life, and simplify the preparation process and improve production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126407200000091
    Figure BDA0005126407200000091
  • Figure BDA0005126407200000092
    Figure BDA0005126407200000092
  • Figure BDA0005126407200000101
    Figure BDA0005126407200000101
Patent Text Reader

Abstract

The invention provides a super-strong weather-resistant rock plate and steel grit double-component ceramic tile back adhesive and a preparation method thereof, the back adhesive comprises a powder component and an emulsion component, the powder component comprises Portland cement, quartz sand, carborundum, a water reducing agent, latex powder and the like, and the emulsion component comprises an acrylic emulsion, a dispersing agent, a defoaming agent, a coalescing agent, deionized water and the like. Wherein the water reducing agent can be a polycarboxylic acid water reducing agent or a naphthalene-based high-efficiency water reducing agent; the latex powder is prepared from vinyl acetate-ethylene copolymerized rubber powder, styrene-acrylate and vinyl acetate homopolymerized rubber powder according to a specific proportion. And the dispersing agent, the defoaming agent and the coalescing agent have various choices. The preparation method comprises the following steps: respectively preparing the powder component and the emulsion component, mixing the powder component and the emulsion component in proportion, and carrying out ultrasonic-assisted stirring. The ceramic tile back adhesive disclosed by the invention has super-strong weather resistance, good bonding strength and chemical corrosion resistance, is suitable for various building scenes, and provides a reliable solution for ceramic tile adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tile adhesive, and in particular to a super-weather-resistant rock plate diamond steel sand two-component tile adhesive and a preparation method thereof. Background Art

[0002] In the field of building decoration, ceramic tiles are a widely used decorative material, and their pasting and fixing technology has always been valued. Traditional ceramic tile pasting mainly relies on cement mortar, but with the improvement of ceramic tile materials, such as vitrified tiles with low water absorption, polished tiles, etc., traditional pasting materials can no longer meet the bonding requirements, resulting in frequent hollowing and falling of ceramic tiles. In order to solve this problem, ceramic tile adhesive came into being, which effectively reduces the risk of hollowing and falling by improving the bonding strength between ceramic tiles and adhesive materials.

[0003] However, there are some shortcomings in the tile adhesive of the prior art. First, the weather resistance is not satisfactory. With the passage of time and the continuous influence of the natural environment, including long-term sun exposure, rain, high and low temperature changes, and humidity fluctuations, the existing tile adhesive is prone to aging, brittleness, cracking, etc. This will not only destroy the overall beauty of the building, but more seriously may cause the tiles to fall off, posing a potential threat to personal and property safety. For example, in the outdoors or in areas with harsh climatic conditions, the existing adhesives often cannot withstand long-term tests and cannot provide stable and lasting adhesion for tiles.

[0004] Secondly, there is a lot of room for improvement in bonding strength. The existing adhesive has limited adaptability to different types of tiles and complex base surfaces. On some special substrates, such as new tiles with low water absorption or smoother base surfaces, the adhesive is not strong enough to bond with the tiles and base, which can easily lead to hollowing. Moreover, after a period of time, due to the influence of various factors, the bonding strength will gradually decrease, which cannot meet the requirements of long-term stable bonding of tiles.

[0005] Furthermore, chemical corrosion resistance needs to be improved. In actual use environments, tiles may come into contact with chemicals such as acids, alkalis, and salts, such as acid rain, detergents, and chemical seepage from building materials. Existing adhesives are easily corroded in these environments, resulting in reduced performance and shortened service life. Especially in some industrial environments or special places, higher chemical corrosion resistance is required for adhesives, but existing products often fail to meet this requirement.

[0006] In addition, there are also problems in the preparation process. The existing adhesive often has uneven stirring during the stirring process, resulting in uneven distribution of ingredients, which affects the performance stability of the adhesive. At the same time, there are also differences in the compatibility between different ingredients, which may cause stratification and precipitation during use, further reducing the quality of the adhesive. Moreover, the existing preparation process does not accurately control parameters such as temperature and rotation speed, which will also affect the final performance of the adhesive. Summary of the invention

[0007] In view of this, the present invention proposes a super-weather-resistant rock plate diamond corundum two-component tile backing adhesive and a preparation method thereof to solve the above problems.

[0008] The technical solution of the present invention is achieved as follows: a super-strong weather-resistant rock plate corundum two-component tile backing adhesive: it includes a powder component and an emulsion component, the powder component includes the following raw materials in parts by weight: 35-55 parts of silicate cement, 30-40 parts of quartz sand, 10-15 parts of corundum, 1-3 parts of water reducer, 5-8 parts of latex powder; the emulsion component includes the following raw materials in parts by weight: 30-50 parts of acrylic emulsion, 1-3 parts of dispersant, 0.5-1.5 parts of defoamer, 3-5 parts of film-forming aid, 40-50 parts of deionized water; the quartz sand is passed through an 80-120 mesh sieve, and the corundum is passed through a 20-40 mesh sieve.

[0009] Furthermore, the powder component includes the following raw materials in parts by weight: 45 parts of silicate cement, 35 parts of quartz sand, 12 parts of corundum, 2 parts of polycarboxylic acid water reducer, and 7 parts of latex powder; the emulsion component includes the following raw materials in parts by weight: 40 parts of acrylic emulsion, 2 parts of sodium polyacrylate dispersant, 1 part of silicone defoamer, 4 parts of alcohol ester twelve film-forming aid, and 45 parts of deionized water.

[0010] Furthermore, the water reducer is a polycarboxylate water reducer or a naphthalene-based high-efficiency water reducer.

[0011] Furthermore, the latex powder is vinyl acetate-ethylene copolymer rubber powder, styrene-acrylate and vinyl acetate homopolymer rubber powder in a mass ratio of (23-28):(10-18):(2-7).

[0012] Furthermore, the dispersant is one or a combination of sodium polyacrylate, sodium hexametaphosphate or sodium tripolyphosphate.

[0013] Furthermore, the defoamer is one or a combination of silicone defoamer, mineral oil defoamer or polyether defoamer.

[0014] Furthermore, the film-forming aid is any one or a combination of propylene glycol phenyl ether, dodecyl alcohol ester, ethylene glycol phenyl ether, propylene glycol methyl ether acetate and dipropylene glycol butyl ether.

[0015] Furthermore, a method for preparing a super-weather-resistant rock plate gold steel sand two-component tile adhesive comprises the following steps:

[0016] S1. Preparation of powder component: adding silicate cement, quartz sand, corundum, polycarboxylate water reducer and latex powder into a dry powder mixer, stirring at a speed of 500-700 rpm for 15-25 minutes at a stirring temperature of 20-30° C. to obtain a powder component;

[0017] S2, preparation of emulsion component: adding acrylic emulsion, dispersant, defoamer, film-forming aid and deionized water into a stirring kettle, stirring at a speed of 800-1000 rpm for 20-30 minutes at a stirring temperature of 25-35° C. to obtain an emulsion component;

[0018] S3. Preparation of two-component tile adhesive: Mix the powder component and the emulsion component at a weight ratio of 1:1.5-3.5, and stir evenly using an ultrasonic-assisted mixer until there are no obvious particles to form a uniform tile adhesive.

[0019] Furthermore, the stirring rate of S3 is 1200-1800 rpm, and the stirring temperature is 38-45°C.

[0020] Furthermore, the ultrasonic frequency of S3 is 20-100 kHz, the ultrafiltration power is 100-500 W, and the ultrasonic time is 10-20 minutes.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The super-weather-resistant rock plate gold steel sand two-component tile adhesive of the present invention can maintain good performance stability in various complex natural environments such as long-term sun exposure, rain, high temperature, low temperature and large changes in humidity. It has excellent performance after artificial climate aging test and natural exposure test, effectively resists aging and cracking, ensures that the tile and the base are firmly and lastingly bonded, and improves the beauty and safety of the building. In terms of bonding strength, through the carefully formulated powder and emulsion components and specific preparation process, it has good adaptability to different types of tiles and base materials, avoids hollowing, and has higher bonding strength and can withstand external forces. It has excellent chemical corrosion resistance, has strong resistance to chemical substances such as acid, alkali, and salt, and is suitable for complex use scenarios. In terms of preparation process, the powder and emulsion are stirred and prepared at specific temperature and speed respectively to ensure that the components are fully and evenly mixed, improve performance stability and production efficiency, and the two-component adhesive adopts ultrasonic assisted stirring to further eliminate particles, make the adhesive more delicate, better play the role of each component, improve the bonding effect, and the preparation process parameters are clear, easy to operate and control, which is conducive to large-scale production and promotion and application. DETAILED DESCRIPTION

[0023] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0024] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0025] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0026] Example 1

[0027] A super-weather-resistant rock plate corundum two-component tile adhesive comprises a powder component and an emulsion component, wherein the powder component comprises the following raw materials in parts by weight: 35 parts of silicate cement, 30 parts of quartz sand, 10 parts of corundum, 1 part of water reducer, and 5 parts of latex powder; the emulsion component comprises the following raw materials in parts by weight: 30 parts of acrylic emulsion, 1 part of dispersant, 0.5 part of defoamer, 3 parts of film-forming aid, and 40 parts of deionized water; the quartz sand is sieved through an 80-mesh sieve, and the corundum is sieved through a 20-mesh sieve;

[0028] The water reducer is a polycarboxylate water reducer;

[0029] The latex powder is a vinyl acetate-ethylene copolymer rubber powder, styrene-acrylate and vinyl acetate homopolymer rubber powder in a mass ratio of 23:10:2;

[0030] The dispersant is sodium polyacrylate;

[0031] The defoamer is an organosilicon defoamer;

[0032] The film-forming aid is propylene glycol phenyl ether.

[0033] Example 2

[0034] A super-weather-resistant rock plate corundum two-component tile adhesive comprises a powder component and an emulsion component, wherein the powder component comprises the following raw materials in parts by weight: 55 parts of silicate cement, 40 parts of quartz sand, 15 parts of corundum, 3 parts of water reducer, and 8 parts of latex powder; the emulsion component comprises the following raw materials in parts by weight: 50 parts of acrylic emulsion, 3 parts of dispersant, 1.5 parts of defoamer, 5 parts of film-forming aid, and 50 parts of deionized water; the quartz sand is sieved through a 120-mesh sieve, and the corundum is sieved through a 40-mesh sieve;

[0035] The water reducer is a naphthalene-based high-efficiency water reducer;

[0036] The latex powder is vinyl acetate-ethylene copolymer rubber powder, styrene-acrylate and vinyl acetate homopolymer rubber powder in a mass ratio of 28:18:7;

[0037] The dispersant is sodium hexametaphosphate;

[0038] The defoamer is a mineral oil defoamer;

[0039] The film-forming aid is ethylene glycol phenyl ether.

[0040] Example 3

[0041] A super-weather-resistant rock plate corundum two-component tile adhesive comprises a powder component and an emulsion component, wherein the powder component comprises the following raw materials in parts by weight: 45 parts of silicate cement, 35 parts of quartz sand, 12 parts of corundum, 2 parts of polycarboxylic acid water reducer, and 7 parts of latex powder; the emulsion component comprises the following raw materials in parts by weight: 40 parts of acrylic emulsion, 2 parts of sodium polyacrylate dispersant, 1 part of organosilicon defoamer, 4 parts of alcohol ester twelve film-forming aid, and 45 parts of deionized water; the quartz sand is passed through a 100-mesh sieve, and the corundum is passed through a 30-mesh sieve;

[0042] The water reducer is a naphthalene-based high-efficiency water reducer;

[0043] The latex powder is vinyl acetate-ethylene copolymer rubber powder, styrene-acrylate and vinyl acetate homopolymer rubber powder in a mass ratio of 25:15:5;

[0044] The dispersant is sodium polyacrylate and sodium hexametaphosphate in a mass ratio of 1:1;

[0045] The defoamer is a silicone defoamer, a mineral oil defoamer or a polyether defoamer in a mass ratio of 1:2:1;

[0046] The film-forming aid is dipropylene glycol butyl ether;

[0047] The above examples 1-3 adopt the following preparation method:

[0048] S1. Preparation of powder component: adding silicate cement, quartz sand, corundum, polycarboxylate water reducer and latex powder into a dry powder mixer, stirring at a speed of 600 rpm for 20 minutes at a stirring temperature of 25° C. to obtain a powder component;

[0049] S2, preparation of emulsion component: adding acrylic emulsion, dispersant, defoamer, film-forming aid and deionized water into a stirring kettle, stirring at a speed of 900 rpm for 25 minutes at a stirring temperature of 30° C. to obtain an emulsion component;

[0050] S3. Preparation of two-component tile adhesive: Mix the powder component and the emulsion component in a weight ratio of 1:2.5, and stir evenly using an ultrasonic-assisted mixer at a stirring rate of 1500rpm, a stirring temperature of 40°C, an ultrasonic frequency of 60kHz, an ultrafiltration power of 300W, and an ultrasonic time of 15 minutes, until there are no obvious particles and a uniform tile adhesive is formed.

[0051] Example 4

[0052] A super-weather-resistant rock plate corundum two-component tile adhesive comprises a powder component and an emulsion component, wherein the powder component comprises the following raw materials in parts by weight: 45 parts of silicate cement, 35 parts of quartz sand, 12 parts of corundum, 2 parts of polycarboxylic acid water reducer, and 7 parts of latex powder; the emulsion component comprises the following raw materials in parts by weight: 40 parts of acrylic emulsion, 2 parts of sodium polyacrylate dispersant, 1 part of organosilicon defoamer, 4 parts of alcohol ester twelve film-forming aid, and 45 parts of deionized water; the quartz sand is passed through a 100-mesh sieve, and the corundum is passed through a 30-mesh sieve;

[0053] The water reducer is a naphthalene-based high-efficiency water reducer;

[0054] The latex powder is vinyl acetate-ethylene copolymer rubber powder, styrene-acrylate and vinyl acetate homopolymer rubber powder in a mass ratio of 25:15:5;

[0055] The dispersant is sodium polyacrylate and sodium hexametaphosphate in a mass ratio of 1:1;

[0056] The defoamer is a silicone defoamer, a mineral oil defoamer or a polyether defoamer in a mass ratio of 1:2:1;

[0057] The film-forming aid is dipropylene glycol butyl ether;

[0058] The above-mentioned Example 4 adopts the following preparation method:

[0059] S1. Preparation of powder component: adding silicate cement, quartz sand, corundum, polycarboxylate water reducer and latex powder into a dry powder mixer, stirring at a speed of 500 rpm for 15 minutes at a stirring temperature of 20° C. to obtain a powder component;

[0060] S2, preparation of emulsion component: adding acrylic emulsion, dispersant, defoamer, film-forming aid and deionized water into a stirring kettle, stirring at a speed of 800 rpm for 20 minutes at a stirring temperature of 25° C. to obtain an emulsion component;

[0061] S3. Preparation of two-component tile adhesive: Mix the powder component and the emulsion component in a weight ratio of 1:1.5, and stir evenly using an ultrasonic-assisted mixer at a stirring rate of 1200 rpm, a stirring temperature of 38°C, an ultrasonic frequency of 20 kHz, an ultrafiltration power of 100 W, and an ultrasonic time of 10 minutes, until there are no obvious particles and a uniform tile adhesive is formed.

[0062] Example 5

[0063] A super-weather-resistant rock plate corundum two-component tile adhesive comprises a powder component and an emulsion component, wherein the powder component comprises the following raw materials in parts by weight: 45 parts of silicate cement, 35 parts of quartz sand, 12 parts of corundum, 2 parts of polycarboxylic acid water reducer, and 7 parts of latex powder; the emulsion component comprises the following raw materials in parts by weight: 40 parts of acrylic emulsion, 2 parts of sodium polyacrylate dispersant, 1 part of organosilicon defoamer, 4 parts of alcohol ester twelve film-forming aid, and 45 parts of deionized water; the quartz sand is passed through a 100-mesh sieve, and the corundum is passed through a 30-mesh sieve;

[0064] The water reducer is a naphthalene-based high-efficiency water reducer;

[0065] The latex powder is vinyl acetate-ethylene copolymer rubber powder, styrene-acrylate and vinyl acetate homopolymer rubber powder in a mass ratio of 25:15:5;

[0066] The dispersant is sodium polyacrylate and sodium hexametaphosphate in a mass ratio of 1:1;

[0067] The defoamer is a silicone defoamer, a mineral oil defoamer or a polyether defoamer in a mass ratio of 1:2:1;

[0068] The film-forming aid is dipropylene glycol butyl ether;

[0069] The above-mentioned Example 5 adopts the following preparation method:

[0070] S1. Preparation of powder component: adding silicate cement, quartz sand, corundum, polycarboxylate water reducer and latex powder into a dry powder mixer, stirring at a speed of 700 rpm for 25 minutes at a stirring temperature of 30° C. to obtain a powder component;

[0071] S2, preparation of emulsion component: adding acrylic emulsion, dispersant, defoamer, film-forming aid and deionized water into a stirring kettle, stirring at a speed of 1000 rpm for 30 minutes at a stirring temperature of 35° C. to obtain an emulsion component;

[0072] S3. Preparation of two-component tile adhesive: Mix the powder component and the emulsion component in a weight ratio of 1:3.5, and stir evenly using an ultrasonic-assisted mixer at a stirring rate of 1800 rpm, a stirring temperature of 45°C, an ultrasonic frequency of 100 kHz, an ultrafiltration power of 500 W, and an ultrasonic time of 20 minutes, until there are no obvious particles and a uniform tile adhesive is formed.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 3 is that the tile backing adhesive includes a powder component and an emulsion component, and the powder component includes the following raw materials in parts by weight: 15 parts of silicate cement, 45 parts of quartz sand, 18 parts of corundum, 5 parts of water reducing agent, and 3 parts of latex powder.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 3 is that the tile backing adhesive includes a powder component and an emulsion component, and the emulsion component includes the following raw materials in parts by weight: 55 parts of acrylic emulsion, 5 parts of dispersant, 0.3 parts of defoaming agent, 6 parts of film-forming aid, and 30 parts of deionized water.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 3 is that no latex powder is added to the powder component.

[0079] Test Example 1- Bond Strength Test

[0080] (1) Tensile bond strength test: According to the relevant standard (JC / T547-2017 Ceramic Tile Adhesive), the ceramic tile is adhered to the ceramic plate with the adhesive backing. After curing for 28 days at a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%, a tensile testing machine is used to apply a tensile force perpendicular to the bonding surface at a speed of 5 mm / min until the ceramic tile is separated from the substrate. The maximum tensile force value is recorded and the tensile bond strength is calculated.

[0081] (3) Shear bond strength test: Use a shear test device to bond the tile to the substrate with the adhesive, and then apply a shear force parallel to the bonding surface. This simulates the ability of the adhesive to resist horizontal external forces (horizontal forces generated by wall deformation) on the tile. During the test, the maximum force value at shear failure is recorded, and the shear bond strength is calculated to provide data support for the adhesive's ability to resist shear forces in actual applications.

[0082] Table 1:

[0083] Group Tensile bond strength (MPa) Shear bond strength (MPa) Example 1 1.5 1.2 Example 2 1.8 1.4 Example 3 2.2 1.8 Example 4 1.7 1.3 Example 5 1.6 1.25 Comparative Example 1 1.0 0.8 Comparative Example 2 1.1 0.9 Comparative Example 3 1.2 1.0

[0084] Test Example 2-Weather Resistance Test

[0085] (1) Artificial climate aging test: Use an artificial climate aging chamber to simulate the natural environment's light, temperature changes, humidity changes, rainfall and other factors. Place the test piece coated with adhesive and pasted with tiles in the aging chamber for 2000 hours. After the aging cycle, observe whether the tiles have fallen off or hollowed out, and conduct a bonding strength test.

[0086] Bond strength retention rate Where P is the bonding strength retention rate, S a is the bonding strength after aging (unit: MPa), S b Bond strength before aging (unit: MPa)

[0087] Table 2:

[0088]

[0089] Test Example 3-Weather Resistance Test

[0090] (1) Acid and alkali resistance test:

[0091] The test pieces coated with the adhesives of Examples 1-5 and Comparative Examples 1-3 and pasted with tiles were immersed in an acidic solution of pH=2 (simulating an acid rain environment) and an alkaline solution of pH=13 (simulating an alkaline building material exudate environment). After immersion for 28 days, the test pieces were taken out, the bonding of the tiles was observed, and the bonding strength test was performed to evaluate the tolerance of the adhesive in acidic and alkaline environments.

[0092] (2) Salt spray resistance test:

[0093] In the salt spray test chamber, the salt spray concentration (5% NaCl solution), spray pressure (150kPa), temperature (35°C) and time (720 hours) are set according to the relevant standards (GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes"). The test pieces coated with adhesive and pasted with tiles are placed in the salt spray chamber to simulate the performance of the adhesive in coastal or high-salt environments. After the test, the bonding state of the tiles and the corrosion of the adhesive surface are checked to evaluate their salt spray resistance.

[0094] Table 3: Acid resistance

[0095]

[0096]

[0097] Table 4: Alkali resistance

[0098]

[0099]

[0100] Table 5: Salt spray resistance

[0101]

[0102]

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A super weather-resistant rock plate gold steel sand two-component tile adhesive, characterized by: The invention comprises a powder component and an emulsion component. The powder component comprises the following raw materials in parts by weight: 35-55 parts of silicate cement, 30-40 parts of quartz sand, 10-15 parts of corundum, 1-3 parts of water reducing agent and 5-8 parts of latex powder; the emulsion component comprises the following raw materials in parts by weight: 30-50 parts of acrylic emulsion, 1-3 parts of dispersant, 0.5-1.5 parts of defoaming agent, 3-5 parts of film-forming aid and 40-50 parts of deionized water; the quartz sand is sieved through an 80-120 mesh sieve, and the corundum is sieved through a 20-40 mesh sieve.

2. The super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1, characterized in that: The invention comprises a powder component and an emulsion component. The powder component comprises the following raw materials in parts by weight: 45 parts of silicate cement, 35 parts of quartz sand, 12 parts of corundum, 2 parts of polycarboxylic acid water reducer, and 7 parts of latex powder; the emulsion component comprises the following raw materials in parts by weight: 40 parts of acrylic emulsion, 2 parts of sodium polyacrylate dispersant, 1 part of organosilicon defoamer, 4 parts of alcohol ester twelve film-forming aid, and 45 parts of deionized water.

3. The super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1 or 2, characterized in that: The water reducer is a polycarboxylate water reducer or a naphthalene-based high-efficiency water reducer.

4. The super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1 or 2, characterized in that: The latex powder is vinyl acetate-ethylene copolymer rubber powder, styrene-acrylate and vinyl acetate homopolymer rubber powder in a mass ratio of (23-28):(10-18):(2-7).

5. The super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1 or 2, characterized in that: The dispersant is one or a combination of sodium polyacrylate, sodium hexametaphosphate or sodium tripolyphosphate.

6. The super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1 or 2, characterized in that: The defoamer is one or a combination of silicone defoamer, mineral oil defoamer or polyether defoamer.

7. The super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1 or 2, characterized in that: The film-forming aid is any one or a combination of propylene glycol phenyl ether, dodecyl alcohol ester, ethylene glycol phenyl ether, propylene glycol methyl ether acetate and dipropylene glycol butyl ether.

8. The method for preparing a super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1, characterized in that: The following steps are involved: S1. Preparation of powder component: adding silicate cement, quartz sand, corundum, polycarboxylate water reducer and latex powder into a dry powder mixer, stirring at a speed of 500-700 rpm for 15-25 minutes at a stirring temperature of 20-30° C. to obtain a powder component; S2, preparation of emulsion component: adding acrylic emulsion, dispersant, defoamer, film-forming aid and deionized water into a stirring kettle, stirring at a speed of 800-1000 rpm for 20-30 minutes at a stirring temperature of 25-35° C. to obtain an emulsion component; S3. Preparation of two-component tile adhesive: Mix the powder component and the emulsion component in a weight ratio of 1:1.5-3.5, and stir evenly using an ultrasonic-assisted mixer until there are no obvious particles, thereby forming a uniform tile adhesive.

9. The super-weather-resistant rock plate gold steel sand two-component tile adhesive as claimed in claim 1, characterized in that: The stirring rate of S3 is 1200-1800 rpm, and the stirring temperature is 38-45°C.

10. The super-weather-resistant rock slab gold steel sand two-component tile adhesive as claimed in claim 1, characterized in that: The ultrasonic frequency of S3 is 20-100kHz, the ultrafiltration power is 100-500W, and the ultrasonic time is 10-20 minutes.

Citation Information

Patent Citations

  • Vitrified brick gum adhesive

    CN105541229A

  • Water-resistant two-component ceramic tile back adhesive and preparation method thereof

    CN114605926A

Cited By

  • Weather-resistant multifunctional ceramic tile back adhesive and preparation method thereof

    CN121379373A